China-Africa: emerging relations - Sousa, Ivo Carneiro de; Diakite, Ansoumane Douty; Iwaloye, Ojo Olukayode (Saint Joseph Academic Press, 2011)
Keywords: Africa China Congresses; China Africa Congresses; Relations

Comparision of modern cultural tourism in Hong Kong and Macao - Mui, Ho Yan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Fernand Braudel and China - Lau, Nga Lai (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Foreign tourist's perceptions on the world heritage of Macau - Sales, Henrigtte (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Inquiry-Based Teaching and Learning as Cross-Cultural Educational Innovation - Pottier, Susan (University of Saint Joseph, 2011)
Inquiry-based Teaching and Learning is fundamental to modern western Science Education. This thesis argues that improving Science Education within a traditional Chinese educational setting can be realized by introducing Inquirybased Learning as a cross-cultural educational innovation - through the agency of a Science Learning Centre (SLC). The thesis evaluates the impact and uptake of the Inquiry-based approach, as seen through SLC activities that foster the professional development of Science teachers, and that build awareness of the approach at the community level. It also examines the process of establishing a SLC, and regional network, in Macau. The conceptual and substantive factors affecting the cross-cultural transfer of an Inquiry-based Teaching and Learning approach and the development of the SLC are explored through the theoretical lenses of Complexity Theory, Innovation and Change Theory; Social Networking Theory; and a range of Curriculum Development Theories. Central to the thesis is the analysis of three Episodes involving Inquiry-based training programmes facilitated by the SLC, and one Account of the development of the SLC itself: a series of Geoscience Inquiry-based learning workshops in Macau and Hong Kong; an invitational international professional development Training Programme provided in York by the National Science Learning Centre in England; an innovative Master’s in Education degree module which involved learning in an unfamiliar context; and finally, the creation of the Macau Science Learning Centre network as an agency for promoting Science Education in Macau. Furthermore, the thesis analyzes the multi-dimensional roles of the writer as participant, co-teacher, co-facilitator, researcher, ethnographer, theorist, and SLC manager. It incorporates aspects of educational innovation and change, teacher professional training, and the development of collaborative social networks. The research makes a unique contribution to the field of Science Education, especially in terms of the transfer and adaptability of an Inquiry-based approach into a traditionally Chinese educational setting through the agency of a SLC
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Lusofonia, encruzilhadas culturais, Actas da Conferência sobre Lusofonia - Correia, Ana; Sousa, Ivo (Saint Joseph University Press, 2011)

Os Índios Potiguara: memória, asilo e poder - Simões, José Manuel (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations PhD in Global Studies (D-GLS); University of Saint Joseph

The invention of colonial Macau in Smirnoff's Paintings (1944-1945) - Lei, Seng U. (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The urban system of the “Portuguese” city of Macau: inventory of the parish model and heritage patterns - Lao, Fong I. (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Urban design study for the waterfront area in NAPE: architects perceptions and cultural alternatives - Ma, Sarah (University of Saint Joseph, 2008)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph